Are the Grimm Tales Traditional? ATU 451, The Maiden Who Seeks Her Brothers, in KHM and in Oral Traditions. - Vaz da Silva, Francisco (The Brothers Grimm and the Folktale: Narrations, Readings, Transformations, 2012)
The expression “oral literature,” being an oxymoron, aptly captures the composite nature of many Kinder- und Hausmärchen texts. In the wake of pioneering works by Ernest Tonnelat and Heinz Rölleke, one aspect of this composite nature—namely, the literary embellishments the Grimm Brothers inflicted on their tales—has been foregrounded. This lecture addresses another, less explored, aspect of the composite nature of KHM. It asks, do the Grimm tales convey traditional themes, can they be deemed traditional? To answer, the discussion proposes an intertextual reading of KHM texts pertaining to ATU 451 and related tale types, and places these texts in the wider context of oral variants. By and by, a number of stable motifs in the Grimm tales and in oral traditions appear as allomotifs, and some shared underlying meanings emerge from this comparative exercise.